ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. SAPTA MULIA JAYA - Hadinata, NG. Youngki (EKONOMIA, 2019)
The purpose of the research is to find out the cash receipt and expenditure information system applied by PT. Sapta Mulia Jaya is in accordance with the elements of internal control.An accounting information system is a system that processes data and transactions to produce useful information for planning, controlling, and operating a business.The analytical tool used is comparing internal control systems and flowcharts according to the theory applied to PT. Sapta Mulia Jaya and a questionnaire.The results of the analysis that have been stated, it can be seen that the organizational structure that separates functional responsibilities is expressly sufficiently appropriate, the system of authority and recording procedures that provide sufficient protection against wealth, debt, income, and costs (organizational structure that separates functional responsibilities firm), healthy practice in carrying out the duties and functions of each organizational unit (cash receipts and disbursements from purchases are made in cash and accompanied by BKK which is used for proof not by check), employees whose quality is in accordance with responsibility (the company does not follow include employees in the training because the company has a reason that the company already knows the ability of employees).